2020
DOI: 10.1111/apps.12255
|View full text |Cite
|
Sign up to set email alerts
|

Prompting Metacognition During a Job Search: Evidence from a Randomized Controlled Trial with University Job Seekers

Abstract: Searching for a job is a self‐directed activity that requires self‐regulation over significant periods of time; yet, in the scientific community, we know little about proximal support interventions that shape the self‐regulation processes during a job search. Using an experimental design, we tested a proximal support intervention in the form of metacognitive prompts and how this shaped metacognition and effort in 123 university job seekers over a period of 9 weeks. Job seekers who were exposed to the intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 75 publications
(126 reference statements)
2
7
0
Order By: Relevance
“…not "one-size-fits-all"(Norem & Chang, 2002) but that it should be considered as part of a broader set of mechanisms and interventions available to career counselors and unemployment organizations(van Woerkom et al, 2021). While our findings suggest promise and are in line with prior job search research on online prompts(Kanar & Bouckenooghe, 2021), it is crucial to acknowledge the…”
supporting
confidence: 61%
See 2 more Smart Citations
“…not "one-size-fits-all"(Norem & Chang, 2002) but that it should be considered as part of a broader set of mechanisms and interventions available to career counselors and unemployment organizations(van Woerkom et al, 2021). While our findings suggest promise and are in line with prior job search research on online prompts(Kanar & Bouckenooghe, 2021), it is crucial to acknowledge the…”
supporting
confidence: 61%
“…While we acknowledge the importance of exploring potential variations in the intervention's effectiveness among different subgroups of job seekers, it should be noted that our study had a relatively modest sample size. Therefore, we were not able to draw any conclusions regarding possible subgroup (Kanar & Bouckenooghe, 2021;Turban et al, 2009).…”
Section: Limitations and Future Research Directionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Future research might examine the effectiveness of informational interviews when paired with other interventions such as (1) e‐learning modules such as BRIO (described before) prior to the informational interview,(2) weekly metacognitive prompts (e.g., 3–5 weekly self‐assessment questions about progress and strategies used while networking: see Kanar & Bouckenooghe, 2021 for an application in job search) after the informational interview, or (3) having students conduct multiple informational interviews with different people. Preinterview, we expect an e‐learning intervention such as BRIO could lessen hesitancy about networking and encourage people to reach out to “weaker” and higher‐status network ties, thereby potentially increasing the benefits of informational interviews (Granovetter, 1995; Van Hoye et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between grit and metacognition found in the present research can be attributed to the metacognitive processes in which individuals and teams engage in, during crucial decision making tasks ( McCarthy and Garavan, 2008 ). Metacognition has been studied in conjunction with theory of mind, social cognition and self-regulation ( Baker et al, 2020 ) and it has also been identified important to study job-seeking behaviours and job-search outcomes, as the process of seeking and finding jobs requires metacognitive skills, implying the ability to set goals, plan, develop and strategise their job search progress and job performance ( Mikulecky and Ehlinger, 1986 ; Turban et al, 2009 ; Kanar and Bouckenooghe, 2021 ). The other transpersonal capital of optimism also positively correlates with grit, consistent with previous studies ( Steinfort, 2015 ; Clement et al, 2020 ; Loftus et al, 2020 ; Oriol et al, 2020 ; Kim and Lee, 2021 ).…”
Section: Discussionmentioning
confidence: 99%